Body composition as an indicator of the nutritional status in children with newly diagnosed ulcerative colitis and Crohn’s disease – a prospective study - Paweł Więch; Monika Binkowska-Bury; Bartosz Korczowski (Gastroenterology Review)
Introduction : The prevalence of nutritional status disorders in children with ulcerative colitis (UC) is much lower than in the case of Crohn’s disease (CD). The largest variability in the components of body composition occurs at the time of a new diagnosis and in periods of disease exacerbation. Aim: Assessment of body composition in children with UC and CD. Material and methods: The preliminary study included 59 children with inflammatory bowel disease (IBD) (34 children with UC vs. 25 children with CD) aged 4–18 years. The final analysis included 26 newly diagnosed children (16 children with UC vs. 10 children with CD). The evaluation of body composition was conducted by means of BIA-101 bioimpedance analyser. Results : Decreased values of lean mass were found in children with newly diagnosed IBD (UC: 41.13 kg vs. control group: 42.06 kg; CD: 35.50 kg vs. control group: 45.50 kg). After a year interval, an increase in fat (UC 1: 7.67 kg vs. UC 2: 10.33 kg; CD 1: 7.36 kg vs. CD 2: 9.47 kg) as well as lean body mass (UC 1: 35.22 kg vs. UC 2: 39.00 kg; CD 1: 35.99 kg vs. CD 2: 42.41 kg) was found in children. Conclusions : Children with newly diagnosed IBD were highly vulnerable to nutritional status disturbances. The increase in fat and lean body mass in an annual interval may be due to the treatment regime and control of the children.